The Braconid and Ichneumonid parasitoid wasps : biology, systematics, evolution and ecology - Quicke, Donald L. J. (Hoboken, NJ : Wiley Blackwell, 2014)
The Ichneumonoidea is a vast and important superfamily of parasitic wasps, with some 60,000 described species and estimated numbers far higher, especially for small-bodied tropical taxa. The superfamily comprises two cosmopolitan families - Braconidae and Ichneumonidae - that have largely attracted separate groups of researchers, and this, to a considerable extent, has meant that understanding of their adaptive features has often been considered in isolation. This book considers both families, highlighting similarities and differences in their adaptations.
Morphology and Biology. Adult External Morphology -- The Ovipositor and Ovipositor Sheaths -- Internal and Reproductive Anatomy -- Immature Stages -- Idiobionts, Koinobionts and Other Life History Traits -- Sex, Courtship and Mating -- Host Location, Associative Learning and Host Assessment -- Overcoming Host Immune Reaction and Physiological Interactions with Host -- Convergent Adaptations -- Taxonomic and Systematic Treatment. Overview of Ichneumonoidea: Relationships and Systematics -- Phylogeny and Systematics of the Braconidae -- Phylogeny and Systematics of the Ichneumonidae -- Ecology and Diversity. Ecology -- Local and Global Patterns in Diversity -- Collecting and Rearing Ichneumonoidea -- Epilogue -- Glossary -- References -- Author Index -- General Index -- Host Index -- Ichneumonoid Genus, Tribe and Subfamily Index -- Ichneumonoidea Species Index.
Includes bibliographical references and index.
Keywords: Parasitic wasps; Braconidae; Ichneumonidae; Parasitic wasps; Parasitoids; Parasitic wasps; Electronic books; Electronic books